Effects of essential oils from two Lippia species on growth of phytopathogenic fungi - Leal, Laura Evelyn (2019)
Chemical characterization of the essential oils of two Lippia species by GC-MS and NMR spectroscopy revealed that limonene(84.3%) and β-caryophyllene (6.1%) were the most abundant components in Lippia turbinata while (6S,7S,10S)-trans-davanone (99.1%)predominated in Lippia integrifolia. Antifungal activity of the essential oils was determined by headspace volatile exposure assay againstthe fungal phytopathogenic Sclerotinia sclerotiorum, Sclerotium rolfsii and Rhizoctonia solani. The essential oil of L. turbinata showedpotent antifungal activity against the panel of fungi tested while that the oil of L. integrifolia significantly inhibited the mycelial growth of S.rolfsii and R. solani.